Klaim Religious Authority dalam Konflik Sunni-Syiâi Sampang Madura - Hamdi, Ahmad Zainul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2012)
This paper deals with the most recent religion-based conflict on the island of Madura involving some Shiâite and their opponents. The conflict took place mid of 2011. The paper traces the history of the conflict, the parties involved in it, and the various factors that triggered it to happen. It argues that although the conflict is local, it nonetheless reflects the larger and most âglobalâ kind of conflict between the Sunnis and the Shiâis. Considering that the Muslims of Madura are always NU in their theology and tradition, the paper asks to what extend does NU lose its influence on the island in this particular regard. Theories concerning conflict will be used to explain this rare development. Preliminary assumption might however be said that the conflict reflects (1) the need of the Madurese agrarian society for a better harmonious state of life, or else (2) the need to punish those who have gone astray from the traditional religious belief, or reflects (3) the latent power struggle between various religious denomination on the island. These are the problems that the paper will try to address.